2018
DOI: 10.1108/jap-10-2017-0034
|View full text |Cite
|
Sign up to set email alerts
|

Through a glass darkly: exploring commissioning and contract monitoring and its role in detecting abuse in care and nursing homes for older people

Abstract: Purpose-The purpose of this paper is to present findings from face-to-face interviews undertaken with 16 care and nursing home managers employed in homes situated in two English local authorities. The research sought to explore managers' perceptions of the role of contract monitoring in the prevention of abuse. Design/methodology/approach-Semi-structured interviews were undertaken with 16 care and nursing home managers. Findings-Though personnel employed by the local authority who conducted contract monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…With this in mind, it is certainly time to look to other fundamental, substantive theory for explanations of why abuse endures in care homes, for example those drawn from social psychology (Moore, 2019c), and consequently, means by which it might be effectively countered. Though inspectors and contract monitoring staff, if suitably experienced and qualified (sometimes they are not, see Moore, 2018b), can provide some direction to care home owners, managers and care staff, what they impart often fails to have any impact because the essential foundations of good, safe care are in part, or in whole, absent. If the personal value frameworks of many staff who are employed in care homes to provide care are incompatible with the work they undertake (Moore, 2017b;Kirkley et al, 2011;Kitwood, 1997), the possibility that abuse will occur and remain unreported endures (Greve, 2008, p. 152;Moore, 2016b, p. 16).…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, it is certainly time to look to other fundamental, substantive theory for explanations of why abuse endures in care homes, for example those drawn from social psychology (Moore, 2019c), and consequently, means by which it might be effectively countered. Though inspectors and contract monitoring staff, if suitably experienced and qualified (sometimes they are not, see Moore, 2018b), can provide some direction to care home owners, managers and care staff, what they impart often fails to have any impact because the essential foundations of good, safe care are in part, or in whole, absent. If the personal value frameworks of many staff who are employed in care homes to provide care are incompatible with the work they undertake (Moore, 2017b;Kirkley et al, 2011;Kitwood, 1997), the possibility that abuse will occur and remain unreported endures (Greve, 2008, p. 152;Moore, 2016b, p. 16).…”
Section: Discussionmentioning
confidence: 99%
“…The practices revealed by respondents are likely to reduce the effectiveness of current regulatory and performance monitoring regimes that remain fundamentally largely unchanged in terms of the incisiveness of methods used since the 1980s and 1990s, respectively. These methods focus predominantly only upon readily observable "organisational artefacts" of the care home and are incapable of penetrating the façade of care home life that is often presented so that they might otherwise reveal the "tacit assumptions", the unspoken organisationally ingrained ways of working, as depicted by Schein (2004, p. 25), for example, that may contribute to the occurrence, concealment and thus perpetuation of abuse (Moore, 2018b). It is in these ways that many of the potential voices that might otherwise reveal the true extent and persistence of abuse in care homes are effectively silenced.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that despite the content of SCRs, SARs and the long procession of abuse enquiries conducted in care homes and hospitals that preceded them, not a great deal of organisational or industry learning has taken place, although this is held as one intended major outcome of such enquiries (Walsh, 2002). The fundamental reasons for why this is the case has not been explored to any significant extent and remains paradoxical, though Moore (2017aMoore ( , 2018a has suggested that it is, in part, due to the flawed methodologies and approaches still used by service commissioners who should be ensuring that they purchase good quality care, and in part, to a long standing, pervasive absence of altruistic motivations among the staff of care home providers, service commissioners and regulators. Moore asserts that both of these phenomena contribute to the obstinacy of abuse in care homes by fostering circumstances under which it can persist, despite the many years of research claiming to identify its causes, and the corresponding developments in safeguarding practice, policy and guidance that have taken place.…”
Section: Reviewing the Literaturementioning
confidence: 99%